2017
DOI: 10.1002/prot.25260
|View full text |Cite
|
Sign up to set email alerts
|

ATLAS: A database linking binding affinities with structures for wild-type and mutant TCR-pMHC complexes

Abstract: The ATLAS (Altered TCR Ligand Affinities and Structures) database (https://zlab.umassmed.edu/atlas/web/) is a manually curated repository containing the binding affinities for wild-type and mutant T cell receptors (TCRs) and their antigens, peptides presented by the major histocompatibility complex (pMHC). The database links experimentally measured binding affinities with the corresponding three dimensional (3D) structures for TCR-pMHC complexes. The user can browse and search affinities, structures, and exper… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
62
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8
1

Relationship

1
8

Authors

Journals

citations
Cited by 63 publications
(63 citation statements)
references
References 40 publications
(55 reference statements)
1
62
0
Order By: Relevance
“…A main reason for this might be the lack of large amounts of experimental data for specific complexes. To increase the amount of relevant data for immune protein complexes, Sirin et al curated the AB‐Bind database for antibody complexes and Borrman et al built the ATLAS database for TCR‐pMHC complexes. The general ΔΔ G predictors, such as FoldX and mCSM, were tested on AB‐Bind data, showing low predictive performance (PCC: 0.34 and 0.35 for FoldX and mCSM, respectively) .…”
Section: Predicting Binding Affinity Changes In Ppismentioning
confidence: 99%
“…A main reason for this might be the lack of large amounts of experimental data for specific complexes. To increase the amount of relevant data for immune protein complexes, Sirin et al curated the AB‐Bind database for antibody complexes and Borrman et al built the ATLAS database for TCR‐pMHC complexes. The general ΔΔ G predictors, such as FoldX and mCSM, were tested on AB‐Bind data, showing low predictive performance (PCC: 0.34 and 0.35 for FoldX and mCSM, respectively) .…”
Section: Predicting Binding Affinity Changes In Ppismentioning
confidence: 99%
“…They can be discerned via sequence landscapes as noted above (47), but have been more traditionally defined as regions where mutations have the greatest impact on binding (57). TCRs where hot spots have been explored through point mutations are listed in a recently developed online database (https://zlab.umassmed.edu/atlas/web/) (58). But point mutants are almost always to alanine, a rather limited exploration of chemical space (51, 59).…”
Section: Rationalizing the Specificity/cross-reactivity Duality Of Tcrsmentioning
confidence: 99%
“…Given that αβ TCRs generally employ a diagonal binding mode to engage pMHC-I antigens where the CDR3α and CDR3β TCR loops form direct contacts with key peptide residues (39, 40), knowledge of the surface features for different epitopes adds an extra layer of information to interpret sequence variability between different viral strains. For other important antigens with known structures in the PDB, such features can be derived from an annotated database connecting pMHC-I/TCR co-crystal structures with biophysical binding data (41), and were recently employed in an artificial neural network approach to predict the immunogenicity of different HLA-A*02:01 bound peptides in the context of tumor neoantigen display (42). A separate study has shown that the electrostatic compatibility between self vs foreign HLA surfaces can be used to determine antibody alloimmune responses (43).…”
Section: Resultsmentioning
confidence: 99%